2016
DOI: 10.1016/j.jcma.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple analyses of factors related to complications in endoscopic sinus surgery

Abstract: Overall, the results of our study showed that the ESS complication rate was 7.8%, with risk factors including advanced Lund-Mackay scores (19-24, odds ratio 10.4) and inexperienced surgeon. It was also noted that ESS with a microdebrider had no impact on complication rates, although the presence of a mesenteric type of anterior ethmoid artery proved to be a protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…[1,2,19] Patients with severe uncontrolled chronic rhinosinusitis are required standard-dose MDCT following sinus surgeries. [1,2,6,22,25] In consideration of the risk of complications, the trial suggested, the adaptation of standard-dose protocols of MDCT for sinus surgeries when severe complications have found by nasal endoscopy and olfactory function test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2,19] Patients with severe uncontrolled chronic rhinosinusitis are required standard-dose MDCT following sinus surgeries. [1,2,6,22,25] In consideration of the risk of complications, the trial suggested, the adaptation of standard-dose protocols of MDCT for sinus surgeries when severe complications have found by nasal endoscopy and olfactory function test.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Postoperative complications affected by the other factors like the experience of surgeons, length of surgeries, and the demographic characters of patients. [6]…”
Section: Introductionmentioning
confidence: 99%
“…Chou et al per 997 patients, there is a direct relationship between the experience of the ENT doctor and the probability of iatrogenic maneuver (a resident doctor has a risk of 12.67% vs. an experienced doctor who has a risk of only 2.4%) 15 .…”
Section: The Role Of the Keros Classification In Endoscopic Sinus Surmentioning
confidence: 99%
“…It could be suspected that using dose reduction CT protocol in chronic rhinosinusitis patients with initially higher risk for perioperative complications, like those with bronchial asthma, after previous sinus surgery and with enhanced nasal polyposis, may potentially further increase the risk of complications [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%